ANALISA PENURUNAN PONDASI TIANG PANCANG KELOMPOK PADA TANAH LUNAK DENGAN METODE TERZAGHI, SKEMPTON-BJERRUM DAN CODUTO - Swijana, I Ketut; Redana, Wayan; Hadiyoto, Bakir (Jurnal Ilmiah Teknik Sipil, 2012)
Pile foundation is utilized to transfer load of structure to foundation soil. The objective of this study is to predict settlement based on field test data. Three methods were utilized which are Terzaghi, Skempton-Bjerrum and Coduto. Based on comparison of prediction and field data it is possible to find correction factor in order to be able to gain a more accurate prediction of settlement. By utilizing published data of building at MIT campus supported using piles undergoing settlements which has been recorded about 20 cm in 48 years. Back analysis undertaken in this study found a correction factor for Terzaghi of about 25.27 %, Skempton-Bjerrum of about 16,59 % and Coduto 6,58 %. In other words the correction factor for Terzagi is 0.747, for Skempton-Bjerrum is 0.834 and Coduto is 0.934. This study concluded that the settlements of piles founded on Surabaya soil by using Terzagi is 7,5281 cm, Skempton-Bjerrum is 6,7529 cm and Coduto is 6,0225 cm. After application of the correction factor as mention above these methods revealed settlements prediction of about 5,6268 cm. This settlement is predicted finished in 25,7672 years.
Keywords: consolidation, settlement, pile-foundation